Análise por meio de espectroscopia de emissão óptica das espécies ativas em nitretação iônica e gaiola catódica - Barbosa, Júlio César Pereira (2007)
Plasma process like ionic nitriding and cathodic cage plasma nitriding are utilized in order to become hard surface of steels. The ionic nitriding is already accepted in the industry while cathodic cage plasma nitriding process is in industrial implementation stage. Those process depend of plasma parameters like electronic and ionic temperature (Te, Ti), species density (ne, ni) and of distribution function of these species. In the present work, the plasma used to those two processes has been observed through Optical Emission Spectroscopy OES technique in order to identify presents species in the treatment ambient and relatively quantify them. So plasma of typical mixtures like N2 H2 has been monitored through in order to study evolution of those species during the process. Moreover, it has been realized a systematic study about leaks, also thought OES, that accomplish the evolution of contaminant species arising because there is flux of atmosphere to inside nitriding chamber and in what conditions the species are sufficiently reduced. Finally, to describe the physic mechanism that acts on both coating techniques ionic nitriding and cathodic cage plasma nitriding